2013
DOI: 10.1002/humu.22333
|View full text |Cite
|
Sign up to set email alerts
|

Exome Resequencing Identifies Potential Tumor-Suppressor Genes that Predispose to Colorectal Cancer

Abstract: Inherited factors account for around one third of all colorectal cancers (CRCs) and include rare high penetrance mutations in APC, MSH2, MSH6, and POLE. Here, we sought novel tumor-suppressor genes that predispose to CRC by exome resequencing 50 sporadic patients with advanced CRC (18 diagnosed ≤35 years of age) at a mean coverage of 30×. To help identify potentially pathogenic alleles, we initially sought rare or novel germline truncating mutations in 1,138 genes that were likely to play a role in colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…For example, ENDOG, mutated in family B (p.R111fs), is a DNase involved in mediating caspase-independent apoptosis 21. DDX31, a RNA-binding protein mutated in family C (p.L367fs), is frequently mutated in medulloblastoma,22 and a germline truncating mutation was observed in a patient with sporadic CRC 23. Family D carries a RGS19 nonsense mutation (p.Q89X), a gene involved in regulating G-protein signalling and autophagy in intestinal cells 24.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ENDOG, mutated in family B (p.R111fs), is a DNase involved in mediating caspase-independent apoptosis 21. DDX31, a RNA-binding protein mutated in family C (p.L367fs), is frequently mutated in medulloblastoma,22 and a germline truncating mutation was observed in a patient with sporadic CRC 23. Family D carries a RGS19 nonsense mutation (p.Q89X), a gene involved in regulating G-protein signalling and autophagy in intestinal cells 24.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, homozygous missense mutations in FANCM (c.5164C>T, p.P1722S) have been found in breast tumors (35), and four different FANCM SNPs have been associated with osteosarcoma risk (36). Also, in colorectal cancer (CRC) patients, an FANCM nonsense mutation (c.5791C>T, p.Arg1931Ter) has been identified (37), but further studies are needed to clarify the potential role of FANCM in CRC susceptibility. However, only one FA patient has been found to carry truncating FANCM mutation and this individual also carries biallelic mutations in the FANCA gene (33,38).…”
Section: Discussionmentioning
confidence: 99%
“…Palles et al [35] analyzed families with this disease, and revealed the role of mutations in POLE and POLD1 genes. Strikingly, these findings received a high number of confirmatory reports [36][37][38][39][40][41][42][43]. Whole exome sequencing and subsequent validation studies on familial melanoma revealed a role of MITF and POT1 mutations; however, their actual impact on the disease incidence remains to be determined [52][53][54][55][56].…”
Section: Other Cancer Typesmentioning
confidence: 76%